If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(-4x+1)=2/3(x=2)
We move all terms to the left:
2(-4x+1)-(2/3(x)=0
Domain of the equation: 3x!=0We multiply parentheses
x!=0/3
x!=0
x∈R
-8x-(2/3x+2=0
We multiply all the terms by the denominator
-8x*3x+2-(2=0
We add all the numbers together, and all the variables
-8x*3x=0
Wy multiply elements
-24x^2=0
a = -24; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·(-24)·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:x=\frac{-b}{2a}=\frac{0}{-48}=0
| 1.5=5d-0/5 | | 4k+8=7k | | 80(160-x)+50x=9800 | | -8-(13+4x)=-3(5-9x)+2 | | 4x+1=0x+6 | | 3x-5(x-4)=-5+2x-9 | | 3x-5(x-4)=-5+2x-5 | | 119+2x+x+21.5=180 | | 15-d=4 | | 7x+28+33=180 | | 3a^2-5a+1=0 | | (x+14)x=20.7 | | Y=0.00005x^2-0.06x | | 49+4y=-9 | | 26+2x-14=90 | | x2=-427 | | (7+35)7=x2 | | 12(y+1)=16(21) | | 4-3q=22 | | −2x+15=−24 | | -27=5d+3 | | 3x+38+x=90 | | 150=-0.43x+405 | | -24=−24-12x | | 4x+5x=12x | | (10+22)10=(13+x)13 | | -24=−24-12b | | 3(x-2)+5x+7=7x-2(x+4) | | x-(9/2)=11 | | x+2/3+x=1-3/4x | | y=-0.43150+405. | | 25.3-7.5x=101.8 |